Flaming creatures - Verevis, Constantine (New York : Columbia University Press, 2019)
Banned soon after its first midnight screenings, Jack Smith's incendiary Flaming Creatures (1963) quickly became a cause célèbre of the New York underground. This study of Smith's magnum opus explores its status as a cult film that appropriates the visual texture, erotic nuance, and overt fabrication of old Hollywood exoticism.
Intro; Table of Contents; Acknowledgments; Introduction; 1. Background and Production; 2. Reception and Controversy; 3. The Film Work: Flaming Creatures; 4. Aftermath and Legacy; Notes; Bibliography; Index
Description based on online resource, title from digital title page (viewed on September 9, 2020).
In English.
Includes bibliographical references and index.
JSTOR
Keywords: Flaming creatures (Motion picture); Flaming creatures (Motion picture); Experimental films -- History and criticism; ART -- Art & Politics; Experimental films; Criticism, interpretation, etc